Predictors of consciousness improvement in patients with hypoglycemic encephalopathy - Lee, Yu Eun; Lee, Eun Ja; Lee, Seung Eun; Park, Jinkyeong (Frontiers in Endocrinology, 2022)
Aims: Hypoglycemic encephalopathy (HE) can cause long-lasting mental changes, disability, and even death. We aimed to investigate prognostic factors for HE and to determine when the treatment of HE becomes futile. Methods: We retrospectively evaluated the data of patients admitted for prolonged HE at Dongguk University Ilsan Hospital between December 2005 and July 2021. We assessed the Glasgow Outcome Scale (GOS) to assess functional outcome. Results: Forty-four patients were enrolled in the study. Thirty-two of these showed the improvement on GOS after treatment. Patients with improved consciousness had a shorter duration of hypoglycemia (1.61.4 vs. 7.815.0 hours, p = 0.04) and a lower incidence of brain lesions than those without improvements in consciousness (76.0% vs. 25.0%, p < 0.01). Patients whose lesions were detected in initial MRIs were 1.3 times less likely to recover consciousness after HE (odds ratios, 1.28; 95% CI, 1.09-1.52; p < 0.01). None of the patients recovered consciousness after 320 h. Maximum time spent to recover was 194 in patients without brain lesions and 319 in those with lesions. Conclusions: Hypoglycemic brain injury detected in initial MRIs predicted poorer HE prognosis. Nevertheless, treatment should be provided for at least for 14 days after admission.